Discovering The Effect of Work From Home and Work Life Balance on Employees’ Work Motivation - Deliza Rahmadona Andera; Odang Kusmayadi (International Journal of Education, Information Technology, and Others, 2023)
This research was conducted with descriptive, verification and quantitative approaches. The population in this study was 202 of the total employees who worked on a Work From Home basis and the sample used was 134 people, so the sampling technique used was non-probability sampling saturated sampling type. Data analysis will use the help of statistical software, SPSS version 26. The results of the descriptive analysis show that all the variables which are Work From Home, Work Life Balance, and Work Motivation are included in the "Strongly Agree" category with a few upgradeable indicators. The results of the verification analysis showed that the results of the partial Work From Home test affected Work Motivation by 0,243. and Work Life Balance affected Work Motivation by 0,508. The results of the simultaneous Work From Home and Work Life Balance tests affected Work Motivation by 53.1% and the remaining 46.9% were influenced by other variables outside this study.